2011
DOI: 10.1111/j.1600-0714.2011.01032.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression form of p53 and PCNA at the invasive front in oral squamous cell carcinoma: correlation with clinicopathological features and prognosis

Abstract: We suggest that it is important to investigate the expression of p53 and PCNA at the invasive front of OSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 31 publications
4
43
0
3
Order By: Relevance
“…Tumour growth is associated with the actions of proliferative proteins such as proliferating cell nuclear antigen (PCNA), a non-histamine nuclear protein that is considered a specific marker of cell division (9,44). The expression of PCNA has been found to be correlated with the degree of malignancy and progression of cancer (45). The strong correlation between PCNA and VEGF detected in the present study indicates that VEGF, which is secreted by neoplastic cells, may induce self-proliferation in an autocrine manner, contributing to neoplastic growth, and induce endothelial cell proliferation and tumour angiogenesis through a paracrine mechanism.…”
Section: Oscc Grade -------------------------------------------------mentioning
confidence: 51%
“…Tumour growth is associated with the actions of proliferative proteins such as proliferating cell nuclear antigen (PCNA), a non-histamine nuclear protein that is considered a specific marker of cell division (9,44). The expression of PCNA has been found to be correlated with the degree of malignancy and progression of cancer (45). The strong correlation between PCNA and VEGF detected in the present study indicates that VEGF, which is secreted by neoplastic cells, may induce self-proliferation in an autocrine manner, contributing to neoplastic growth, and induce endothelial cell proliferation and tumour angiogenesis through a paracrine mechanism.…”
Section: Oscc Grade -------------------------------------------------mentioning
confidence: 51%
“…As an important cell proliferation marker, PCNA plays an essential role in DNA replication and repair [20]. Its expression and distribution are closely associated with the rate of cellular proliferation and DNA synthesis [29]. This study found that the elevated expression of LARP1 correlated positively with PCNA expression, suggesting that LARP1 mediated cancer cell proliferation.…”
Section: Discussionmentioning
confidence: 88%
“…PCNA is a cofactor of DNA polymerase δ which is necessary for cell proliferation, so it is often used as an index of DNA replication and cell proliferation [23]. Tumor PCNA expression in each group were shown in Figure 6C.…”
Section: Resultsmentioning
confidence: 99%